Comparison of Behavioral Compatibility among Students with Different Brain Dominance Patterns (Right, Left) - Ali Burhan Hawar (Wahid Hasyim University, 2026)
Objectives: This study aimed to identify differences in behavioral compatibility among students with different brain dominance patterns, namely right-brain and left-brain dominance. Materials and Methods: This study used a descriptive comparative approach. The population consisted of 44 fourth-year students from the College of Physical Education and Sports Sciences, Kirkuk University. The main sample included 32 students after excluding students who participated in the pilot study, students who did not complete the scales, and students with an integrated brain dominance pattern. Two instruments were used: the Behavioral Compatibility Scale and the Brain Dominance Scale. Data were analyzed using percentage, mean, standard deviation, correlation coefficient, and independent samples t-test through SPSS. Results: The results showed a significant difference in behavioral compatibility between students with right-brain dominance and those with left-brain dominance. Students with right-brain dominance achieved a higher mean score in behavioral compatibility than students with left-brain dominance. Conclusions: Students with right-brain dominance demonstrated better behavioral compatibility than students with left-brain dominance. The findings indicate the importance of considering brain dominance patterns in teaching and training processes, especially in physical education, to support individual differences and improve students’ adaptive behavior.